Selection of lactic acid bacteria with probiotic potential from colonial cheeses - J.A.M. André; L. Balbinot; K.B.P.B. Casaril (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of the present study was to isolate and identify, through phenotypic analyses, lactic acid bacteria from samples of colonial cheeses, with probiotic potential, as well as to evaluate their antimicrobial effects, their tolerance to acidic conditions and their resistance to gastrointestinal tract in a simulated form. Ten samples of colonial cheese (n=10) were used to isolate 100 bacterial cultures. The cultures were phenotypically characterized and tested for resistance to different temperatures, carbohydrate fermentation capacity and growth capacity at different NaCl concentrations. Subsequently, 20 cultures were selected for analysis of antimicrobial activity and susceptibility, tolerance, and resistance to acidic media. It was observed that most of the bacteria presented the form of Gram-positive bacilli (67%) and negative catalase (97%), all showed growth at the evaluated temperatures (10°C and 45°C) and in relation of carbohydrate fermentation, 93% fermented glucose, 99% mannitol and all fermented lactose and sorbitol with gas production, characterizing themselves as heterofermentative. Regarding resistance to different antimicrobials, 75% were resistant to two or more antimicrobials. The survival rate for simulated conditions of the gastrointestinal tract was 15% in acidic medium (pepsin and pH 2) and 90% when acidic medium was associated with milk (pepsin + milk and pH 2), after 240 minutes. They showed longer survival time and excellent resistance in intestinal conditions. It is possible to infer that the LAB present in the colonial cheeses analyzed present promising characteristics to be considered as potentially probiotics.